The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.24940/ijird/2022/v11/i7/jul22009
|View full text |Cite
|
Sign up to set email alerts
|

Framework towards Residential Neighbourhood Crime Prevention in South Western Nigeria

Abstract: The need to curb the soaring trend of residential neighbourhood crime, considering its negative impact on the neighbourhood in general and property value in particular is not to be given the expected attention in academia and government settings. However, the consequences of residential neighbourhood crime are found to be devastating. Hence, this study proposes a Socio-Environmental Design Factors (SEDeF) model for residential neighbourhood crime toward improving property value in Nigeria. Purposive and system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…Secondly, findings from this study also confirm a body of existing studies that has found strong relationship between housing rental values and urban security or insecurity based on levels of crimes (Olajide, 2008; Ceccato and Wilhelmsson, 2011; Mcllhatton et al. , 2016; Tillyer and Walter, 2018; Song et al.…”
Section: Discussion Of Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Secondly, findings from this study also confirm a body of existing studies that has found strong relationship between housing rental values and urban security or insecurity based on levels of crimes (Olajide, 2008; Ceccato and Wilhelmsson, 2011; Mcllhatton et al. , 2016; Tillyer and Walter, 2018; Song et al.…”
Section: Discussion Of Resultssupporting
confidence: 87%
“…Secondly, findings from this study also confirm a body of existing studies that has found strong relationship between housing rental values and urban security or insecurity based on levels of crimes (Olajide, 2008;Ceccato and Wilhelmsson, 2011;Mcllhatton et al, 2016;Tillyer and Walter, 2018;Song et al, 2019). For example in Ibadan, South Western Nigeria Olajide (2008) found that crime intensity had negative correlation with housing values while Song et al (2019) found that a positive correlation between housing prices and criminal activities in China. The negative impact of crime on apartment prices in Stockholm, Sweden was established by Ceccato and Wilhelmsson (2011) and in the Belfast, Ireland region by Mcllhatton et al (2016).…”
Section: Discussion Of Resultssupporting
confidence: 85%
See 3 more Smart Citations